THE SETS (SCIENCE, ENVIRONMENT, TECHNOLOGY, AND SOCIETY) MODEL TO ENHANCE SCIENCE LITERACY OF GRADE IV STUDENTS IN MI MIFTAHUL ULUM GUMAYUN TEGAL - Awaliyah, Asyifa Nur; Rahayu, Devi Budi (Jurnal IPA Terpadu, 2024)
This paper presents the results of research that discusses the use of the Science, Environment, Technology and Society (SETS) model which aims to train the science literacy of fourth grade students at MI Miftahul Ulum Gumayun Tegal. The research is quasi experiment with non-equivalent control group design. The research was conducted in the even semester of the 2023/2024 academic year from June to July 2024. The research subjects were 40 students with details of 20 student in the experimental class and 20 students in the control class. The instruments used were multiple choice test questions, field notes and researcher observation sheets. Based on the results of the study, the use of the SETS model in training the science literacy of MI grade IV students showed a moderate increase, with an average N-Gain 31.7%. The independent sample t-test results show a significance of 0.006. If sig (2-tailed) <0.05 then H1 is accepted. From the research results, it can be concluded that using SETS model can improved the science literacy of fourth grade students at MI Miftahul Ulum Gumayun Tegal.